Association of Polyvascular Disease and Elevated Interleukin-6 With Outcomes in Acute Ischemic Stroke or Transient Ischemic Attack - Tian, Ye; Jing, Jing; Wang, Huijuan; Wang, Anxin; Zhang, Yijun; Jiang, Yong; Lin, Jinxi; Zhao, Xingquan; Li, Hao; Wang, Yongjun; Guo, Li; Meng, Xia (Frontiers in Neurology, 2021)
Background Polyvascular disease (PolyVD) and interleukin (IL)-6 are associated with poor outcomes in patients with stroke respectively. However, whether combined PolyVD and elevated IL-6 levels would increase the risk of poor outcomes of stroke patients is yet unclear. Methods Data were obtained from the Third China National Stroke Registry (CNSR-Ⅲ). PolyVD was defined as acute ischemic stroke (AIS) or transient ischemic attack (TIA) with coronary artery disease (CAD) and/or peripheral artery disease (PAD). Patients were divided into four groups according to the combination of vascular beds number (non-PolyVD or PolyVD) and IL-6 levels ( IL-6<2.64 pg/mL or IL-6≥2.64 pg/mL). The primary outcome was a recurrent stroke at 1-year follow-up. Cox proportional hazard models were employed to identify the association of the combined effect of PolyVD and IL-6 with the prognosis of patients. Results A total of 10773 patients with IL-6 levels and 1-year follow-up were included. The cumulative incidence of recurrent stroke was 9.87% during the 1-year follow-up. Compared to non-PolyVD and IL-6<2.64 pg/mL patients, patients had non-PolyVD with IL-6≥2.64 pg/mL (HR 1.245 95%CI 1.072-1.446; P < .001) and PolyVD with IL-6<2.64 pg/mL (HR 1.251 95%CI 1.002-1.563; P=.04) were associated with an increased risk of recurrent stroke during 1-year follow-up. Likewise, patients with PolyVD and IL-6≥2.64 pg/mL (HR 1.290; 95% CI 1.058-1.572; P=.01) had the highest risk of recurrent stroke at 1-year follow-up among groups. Conclusion PolyVD and elevated IL-6 levels are both associated with poor outcomes in patients with AIS or TIA. Moreover, the combination of them increases the efficiency of stroke risk stratification compared with when used alone. More attention and intensive treatment should be given to those patients with both PolyVD and elevated IL-6 levels.